Skin colonisation at the catheter exit site is strongly associated with catheter colonisation and catheter‐related sepsis. (29th September 2014) - Ponnusamy, Vennila; Perperoglou, Aris; Venkatesh, Vidheya; Curley, Anna; Brown, Nicholas; Tremlett, Catherine; Clarke, Paul
Abstract Aim The commonest mode of catheter colonisation is via the extraluminal route with skin bacteria. Catheter‐related sepsis causes significant mortality and morbidity in neonates. Our aim was to study the relationships between culture‐positive catheter exit site skin swabs, percutaneous central venous catheter segments and blood to determine the magnitude of associations between exit site skin colonisation, catheter colonisation and catheter‐related sepsis. Methods In a prospective study, an exit site skin swab and three formerly in vivo catheter segments (proximal, middle and tip) were taken for culture at catheter removal. In those neonates who were clinically unwell at catheter removal, a peripheral blood culture was also collected. Univariate and multivariate analyses were used to study associations. Results Skin swabs were culture positive in 39 (21%) of 187 catheter removals. With a culture‐positive skin swab, the risk of associated catheter colonisation was nearly eight times higher (OR: 7.84, 95% CI: 3.59–17.15) and the risk of definite catheter‐related sepsis with the same organism was nearly 10 times higher (OR 9.86, 95% CI: 3.13–31.00). Conclusion Culture‐positive skin swabs from the catheter exit site were strongly associated with catheter colonisation and with definite catheter‐related sepsis with the same organism. These data provide further evidence supporting catheter colonisation via the extraluminal route and highlight the importance of optimising skin disinfection before catheter insertion.